Classical Hodgkin Lymphoma Presenting as Cutaneous and Soft Tissue Mass Lesion: An Enigmatic Presentation Posing a Diagnostic Challenge—A Case Report and Review of Literature - Ayushi Shrivastava; Sandeep Jain; Payal Malhotra; Shalini Mishra; Sunil Pasricha; Gauri Kapoor (Indian Journal of Medical and Paediatric Oncology)
Hodgkin lymphoma (HL) is primarily a nodal disease. Cutaneous involvement of HL as a presenting feature is extremely rare. Skin involvement is usually seen as a metachronous involvement in the course of disease and is associated with poor prognosis. Primary skin and soft tissue involvement can be construed as nonhematological, inflammatory, or infective etiology. We report a 14-year-old girl with fever, weight loss, lymphadenopathy, and multiple papular lesions over the right chest wall as initial manifestation of HL, posing a diagnostic challenge. In view of stage IVBE, patient was managed with intensive chemotherapy regimen and is currently free of disease at 6 months of follow-up.